Security of IoT Devices. Issue 1 (2nd January 2018) - Buenrostro, Erick; Cyrus, Daniel; Le, Tra; Emamian, Vahid
ABSTRACT: The network of home devices is the concept of establishing a web of connections using SMART devices in the household. These devices, a part of the Internet of Things (IoT), have expanded the idea of interconnectedness on the Internet. As technology progresses, more devices are given the capability of connecting to a network, creating convenience for users. Within a household specifically, SMART appliances such as washers, dryers, refrigerators and TVs can connect to a network via Bluetooth, Ethernet or Wi-Fi. Although the benefits of IoT devices are significant, so are the potential downsides that can be created when improper implementation of protocols used to communicate information among networks are used. As millions of devices connect to the Internet daily, it is important to measure the security of these connections. Not uncommon to find, a popular trade-off exists between security-implementation cost and actual security levels. In this research, we study proper security implementation of connected household electronic devices for better safeguarding the transmitted data.